Islamic Religious Education Learning Management in Forming the Religious Character of Students - Mumuh Muhtarom; Soeganda Priyatna; Ricky Yoseptry; Nandang Koswara (UIN Sunan Gunung Djati Bandung, 2021)
This research is motivated by the phenomenon of weak religious character behavior shown by high school age teenagers in the city of Bandung. The facts in the field illustrate the tendency of increasing behavioral deviations among high school students, especially in the city of Bandung, this is an indicator that the implementation of Islamic religious education learning in schools is not optimal. Based on the facts of the problem, the formulation of this research problem is about how to management of Islamic religious education learning in shaping the religious character of high school students in the city of Bandung. This research is a type of qualitative research with descriptive method conducted at SMAN 22 and SMAN 27 Bandung. Data collection techniques combine field observations, interviews and documentation studies. The grand theory of this research uses Ricky W. Griffin's management theory. Inductive data analysis resulted in several conclusions, namely: in general, the Management of Islamic Religious Education Learning in Forming the Religious Character of Students at SMAN 22 and SMAN 27 Bandung has been running effectively. Specific conclusions: (1) Development of PAI Learning Management in Forming the Religious Character of Students at SMAN 22 and SMAN 27 Bandung is part of the School's Strategic Plan and has been running even though its implementation has not been optimal; (2) Implementation of PAI Learning Management in Shaping Students' Religious Character at SMAN 22 and SMAN 27 Bandung City has been running in accordance with management functions, but in the implementation stage it still needs improvement and refinement; (3) Supporting Factors of PAI Learning Management in Shaping Students' Religious Character at SMAN 22 and SMAN 27 Bandung City consist of internal factors in the form of high student awareness, high teacher awareness, and the strong role of school policy. As well as external factors in the form of parental guidance, good environmental support and the ability to control the development of information technology in PAI learning; (4) Inhibiting factors of PAI Learning Management in Shaping Students' Religious Character at SMAN 22 and SMAN 27 Bandung in the form of weak student motivation, lack of teacher creativity in developing learning methods, weak parental support and environmental factors and the development of information technology; and (5) Efforts to Overcome Barriers to PAI Learning Management in Shaping Students' Religious Character at SMAN 22 and SMAN 27 Bandung have been carried out through strengthening the competence of PAI teachers, strengthening the implementation of school policies, strengthening communication with parents and stakeholders as well as utilizing digital applications and technological developments. in PAI learning management.